The use of mobile instant messaging for organizational communication in the Malaysian Army / Saiful Azuwar Abd Halim - Saiful Azuwar , Abd Halim (2020)
The adoption of a good communication strategy is crucial to ensure the efficient flow of information and to stimulate active participation in the organization. Policymaker needs to develop communication strategies by considering the fit between the richness of the media and the working environment. Mobile instant messaging (MIM) is the most favoured medium of communication in many organizations, including the military. It is immediate, low-cost, permits real-time communication, and provides group discussion capabilities. However, the use of MIM has created issues in the military work in the aspects of command function, irregularities in the flow of information, work distraction, and compatibility with military doctrine and values. The purpose of this study is to explore the use of MIM in the Malaysian Army as a medium for organizational communication and to provide guidelines for MIM application in the service. The objectives of this study are to identify the current practice of MIM usage in the Malaysian Army, assess the suitability of usage in the Army, and recommend proper guidelines for MIM use in the Army. To achieve these objectives, the Media Richness Theory was employed as a theoretical lens in guiding the data collection and developing an understanding of the phenomenon. The case study research method was employed. Four activities in the Malaysian Army (management, training, operation, and logistics) were selected as a unit of analysis and semi-structured interviews were performed to acquire the relevant data. Twelve respondents with vast working experiences in the Army were purposively selected for the interviews. By using thematic analysis, several interesting findings were unearthed. First, the richness of MIM in providing rapid feedback was most effective in management and logistics, with some limitations in training and operations. On the other hand, the richness of the technology in handling multiple cues was decreased due to the absence of non-verbal cues. The capability of MIM to utilize natural languages makes it rich in all activities. Finally, MIM as a medium is rich since it can establish personal focus during working interaction with some limitations. As a result, the Army needs to reexamine its application of MIM at the workplace and provides the guidelines for policymakers, commanders, and managers.